FORMULASI KRIM MINYAK ALPUKAT (Avocado oil) DAN EFEKTIVITASNYA TERHADAP XEROSIS PADA TUMIT KAKI - Febia Sari; Didi Nurhadi Illian; Ovalina Sylvia Br. Ginting (Universitas Haji Sumatera Utara, 2022)
Xerosis is dry and cracked skin condition commonly in heel caused by losing of water content in stratum corneum skin lipid and natural moisturizing factor.The purpose of this study is to formulate a cream for treatment of xerosis in heel using avocado oil,consisted of avocado oil, cera alba, liquid paraffin, borax, BHT and methyl paraben. Avocado oil concentrations used were 10; 12.5; 15; 17.5 and 20%. Examination of the avocado oil creams include homogenity, measurement of pH, emulsion type, and the stability of the preparation. Stability parameters were odor, color and phase separation during storage of 12 weeks. Activity test of the preparations were performed on xerosis in heel twice a day in every day for 4 weeks. The effectiveness of the cream was tested on 21 volunteers who have xerosis on the heel for 4 weeks. The safety of cream was determined by irritation test used usage test that conducted on 10 volunteers.The results showed that avocado oil could be formulated into a cream preparation that was homogeneous and stable during 12 weeks of storage. Irritation test conducted on 10 volunteers showed that no one got irritation on the skin. Cream with avocado oil concentration of 10% had been able to restore xerosis in heel. The best skin recovery of xerosis in heel visible in avocado oil concentration of 20%. The conclusion of this study is avocado oil could be formulated in a cream. The cream didn’t induce irritation and application of the cream for 4 weeks.